Comparison of Ventifact Orientations and Recent Wind Direction Indicators on the Floor of Jezero Crater, Mars. Issue 3 (24th March 2023) - Herkenhoff, K. E.; Sullivan, R. J.; Newman, C. E.; Paar, G.; Baker, M.; Viúdez‐Moreiras, D.; Ashley, J. W.; Bechtold, A.; Nuñez, J. I.
Abstract: Wind‐abraded rocks and aeolian bedforms have been observed at the Mars 2020 Perseverance landing site, providing evidence for recent and older wind directions. This study reports orientations of aeolian features measured in Perseverance images to infer formative wind directions. It compares these measurements with orbital observations, climate model predictions, and wind data acquired by the Mars Environmental Dynamics Analyzer. Three‐dimensional orientations of flute textures on rocks, regolith wind tails extending from behind obstacles, and other aeolian features were measured using Digital Terrain Models derived from Mastcam‐Z and navigation camera (Navcam) stereo images. Orientations of rock flutes measured in images acquired through Sol (Martian day) 400 yielded a mean azimuth of 94° ± 7° (wind from the west). However, similar measurements of regolith wind tails indicate that recent sand‐driving winds have been blowing from the east‐southeast, nearly the opposite direction (mean azimuth = 285° ± 15°). Atmospheric modeling generally predicts net annual sand transport from the east‐southeast at present, consistent with Perseverance regolith wind tail and orbital observations. The orientation of ventifact flutes thus suggests that they were formed under a different climate regime. Differences in orientations of recent and paleo‐wind indicators have been noted at other Mars landing sites and may result from major orbital/axial changes that can cause significant changes in atmospheric circulation. Orientation differences between modern and older wind direction indicators at Jezero are useful clues to the climate history of the region. Plain Language Summary: Strong winds mobilize sand grains that can abrade rock surfaces to form lineated bedrock features. These wind abrasion textures record the direction of the sand‐driving winds that created them. Wind abrasion textures were observed on rocks on the floor of Jezero crater traversed during the early part of the Mars 2020 mission. Orientations of these abrasion textures were measured using rover‐acquired three‐dimensional stereo image data. Results indicate that the sand‐driving wind directions that abraded these rocks are very different—nearly opposite—from the current strongest wind directions indicated by orientations of sandy wind tails extending from behind obstacles, measured wind velocities, and climate model predictions for the area. Collectively, these results provide a record of changing atmospheric circulation patterns in the Jezero region. Key Points: The orientations of linear wind abrasion features on ventifacts record the direction of the ancient winds that formed them Measurements of current and recent wind directions in Jezero crater differ significantly from the inferred direction of ancient winds As observed at other locations on Mars, these differences suggest a change in the climate regime at these locations